Identificação arquivística na gestão documental do Instituto de Gestão Previdenciária do Estado do Pará - ROCHA, Adryelle Roberta da Costa (2018)
Presenting an Archival Identification Model was this research’s purpose to the Instituto de Gestão Previdenciária do Estado do Pará – IGEPREV as an initial proposal to implement a Records Management System aiming at an accumulated documentary mass treatment, applying this archival function that is used as one of the first methods on technical documentary treatment. Justifying how is required this documentary identification based on archivist professional activities. It is characterized as empirical using the method of case study with qualitative approach and participant observation. The theoretical composition was formed to verify concepts of Archival Identification in Spain and Brazil, to analyze Records Management procedures and techniques aiming at a development of a model of Archival Identification. The research result indicates organ’s characteristics, collection’s characteristics, the development of an applied and analyzed form justifying the Archival Identification function as a relevant technique to handle the documentary mass on its production and accumulated documentary mass.